Black Campaign Crimes (Black Campaign) Under the Supervision of the General Election Supervisory Body - ermaharialijana (Faculty of Law, Universitas Pekalongan, 2024)
Elections are a means for the people to participate in determining the direction of government administration. After the amendment to the 1945 Constitution, both the Election of legislative members and the Election of executive power implementers were carried out directly by the people. In carrying out the nomination or contestation stages, which are then continued with the campaign stage, the words/phrases black campaign or black campaign often appear. In general, what is referred to as a black campaign is slandering, pitting against each other, inciting, insulting, or spreading false news carried out by a candidate/group of people/political party/supporter of a candidate against their opponents. If the form is a criticism of the vision, vision, or program of a particular candidate, it is not classified as a black campaign. Black campaigns that can harm Democracy itself. It can also trigger and endanger the unity and integrity of the nation and State's; the rapid development of technology is used as a tool or means to spread false news or hoaxes, slander and SARA issues.